2022
DOI: 10.1002/chem.202200647
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Competitive Decay Channels Leads to Enhanced Coumarin Photochemistry

Abstract: In the development of photolabile protecting groups, it is of high interest to selectively modify photochemical properties with structural changes as simple as possible. In this work, knowledge of fluorophore optimization was adopted and used to design new coumarin‐ based photocages. Photolysis efficiency was selectively modulated by inactivating competitive decay channels, such as twisted intramolecular charge transfer (TICT) or hydrogen‐bonding, and the photolytic release of the neurotransmitter serotonin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 64 publications
(118 reference statements)
1
21
0
3
Order By: Relevance
“…The results in this chapter were previously published in reference [IV] "Inactivation of competitive decay channels leads to enhanced coumarin photochemistry". 270 The spectroscopic data described in this chapter was measured and analyzed by Marvin In Chapter 4.2, a coumarin PPG was used to induce a strand break in an oligonucleotide. Coumarin was selected instead of o-nitrobenzyl in order to use visible light und reduce cell damage.…”
Section: Systematic Improvement Of Coumarin Ppgsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in this chapter were previously published in reference [IV] "Inactivation of competitive decay channels leads to enhanced coumarin photochemistry". 270 The spectroscopic data described in this chapter was measured and analyzed by Marvin In Chapter 4.2, a coumarin PPG was used to induce a strand break in an oligonucleotide. Coumarin was selected instead of o-nitrobenzyl in order to use visible light und reduce cell damage.…”
Section: Systematic Improvement Of Coumarin Ppgsmentioning
confidence: 99%
“…Remaining curves can be found in the supporting information of reference [IV]. 270 It was demonstrated that after ca. 200 photon equivalents, about 90% of the starting material 9b released the neurotransmitter serotonin.…”
Section: Systematic Improvement Of Coumarin Ppgsmentioning
confidence: 99%
“…the competing relaxation pathways [159] from the excited state, the solvent interactions and the leaving group (LG) itself. [148] These factors are often not independent from each other, which makes a rational design rather complicated.…”
Section: Photolabile Protecting Groupsmentioning
confidence: 99%
“…The effects of a large variety of site-specific modifications on such coumarin compounds are well studied and have been reported in numerable original publications and reviews. [148,159,[170][171][172] Considering the potential use in biological systems, (7-diethylaminocoumarin-4-yl)methyl (DEACM) and its variants have become model compounds of choice. Besides the relatively large red-shift towards 370-410 nm -depending on the substituents -DEACMbased PPGs also have an increased uncaging quantum yield (QY).…”
Section: Photolabile Protecting Groupsmentioning
confidence: 99%
See 1 more Smart Citation